2020
DOI: 10.1007/s40430-020-2241-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrically modulated droplet impingement onto hydrophilic and (super)hydrophobic solid surfaces

Abstract: Although the impact of impinging droplets on solid substrates has been widely studied, any possible non-trivial interaction between the substrate wettability and applied electric field toward altering the underlying dynamical characteristics remains unexplored. In this study, the interaction between electric field and hydrodynamic transport, toward influencing the dynamic behavior of a water droplet, dispersed in an immiscible fluid, on solid substrates has been numerically investigated. Finite element simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Although the field of droplet electrohydrodynamics was initiated almost more than fifty years ago [3,4], droplet impact studies in the presence of electric field are few and far between. Khojastech et al [24] performed numerical simulations of dielectric liquid droplet impact under the influence of electric field and reported that the droplet always deformed in the direction of the electric field. Ryu and Lee [25] showed experimentally that the maximum spreading diameter of a charged droplet on a dielectric substrate is more than an uncharged drop.…”
Section: Introductionmentioning
confidence: 99%
“…Although the field of droplet electrohydrodynamics was initiated almost more than fifty years ago [3,4], droplet impact studies in the presence of electric field are few and far between. Khojastech et al [24] performed numerical simulations of dielectric liquid droplet impact under the influence of electric field and reported that the droplet always deformed in the direction of the electric field. Ryu and Lee [25] showed experimentally that the maximum spreading diameter of a charged droplet on a dielectric substrate is more than an uncharged drop.…”
Section: Introductionmentioning
confidence: 99%
“…Modifying the wettability characteristics of a surface can control the movement and deflection of droplets (Nilsson & Rothstein, 2012), transport droplets without using external energy input (i.e. electric field) (Khojasteh et al, 2020) and avoid/promote formation of tiny satellite droplets (Mertaniemi et al, 2011). The methods for fabricating hydrophilic-superhydrophobic patterns were presented by Ueda and Levkin (Ueda & Levkin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…By modifying this parameter, we can simulate different degrees of wettability of the cutting surface, from hydrophilic to hydrophobic properties. [ 37 ] 2κAφn=φ21cosθ. …”
Section: Methodsmentioning
confidence: 99%